2021
DOI: 10.1016/j.apsb.2020.11.002
|View full text |Cite
|
Sign up to set email alerts
|

A novel SIRT6 activator ameliorates neuroinflammation and ischemic brain injury via EZH2/FOXC1 axis

Abstract: Ischemic stroke is the second leading cause of death worldwide with limited medications and neuroinflammation was recognized as a critical player in the progression of stroke, but how to control the overactive neuroinflammation is still a long-standing challenge. Here, we designed a novel SIRT6 activator MDL-811 which remarkably inhibited inflammatory response in lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages and primary mouse microglia, which were abolished by silencing SIRT6. RNA-seq screening iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 61 publications
2
63
0
Order By: Relevance
“…Like the case in U2OS/GR-GFP stable cellbased assay (Figure1d,e), we at first investigated whether IP treatment also inhibited GR nuclear translation in brains of mice. In the test, neurons and microglia in the hippocampus of diabetic mice were identified by MAP2 and Iba1(He et al, 2021) antibodies, respectively, and the results indicated that IP inhibited GR nuclear translocation in microglia (Figure4a-d) and neurons (FigureS8a-d).…”
mentioning
confidence: 95%
“…Like the case in U2OS/GR-GFP stable cellbased assay (Figure1d,e), we at first investigated whether IP treatment also inhibited GR nuclear translation in brains of mice. In the test, neurons and microglia in the hippocampus of diabetic mice were identified by MAP2 and Iba1(He et al, 2021) antibodies, respectively, and the results indicated that IP inhibited GR nuclear translocation in microglia (Figure4a-d) and neurons (FigureS8a-d).…”
mentioning
confidence: 95%
“… 73 Moreover, He et al concluded that the deacetylation of EZH2 through SIRT6 causes an increased association between EZH2 and FOXC1 that exerts anti-inflammatory response, whereas Emelyanov et al, 2018, concluded the positive correlation between dopamine and GATA2 expression in PD. 74 , 75 FOXL1 is implemented in the pathogenesis of NDDs, while NFIC was identified as novel loci in AD. 76 78 Studies demonstrated that HINFP is a coactivator in the sterol-regulated transcription of PCSK9, a target gene of SREBP2 involved in the tau alterations, which contribute to disturbed cholesterol homeostasis in AD.…”
Section: Results and Discussionmentioning
confidence: 99%
“… 91 , 92 Forma et al, 2018, demonstrated that an increased expression of FOXA1 and FOXC1 was associated with increased acetylation levels of histone H3, whereas He et al concluded that increased FOXC1 protein levels in RAW246.7 cells were associated with altered levels of H3 acetylation. 74 , 93 …”
Section: Results and Discussionmentioning
confidence: 99%
“…MDL-811, a recently discovered small-molecule activator of Sirt6, functions as an inhibitor of inflammation in LPS-stimulated mouse macrophages and microglia. The activated Sirt6 was found to deacetylate the enhancer of zeste homolog 2 (EZH2), a histone methyltransferase and ameliorate the neuroinflammation in ischemic brain injury via EZH2/forkhead box C1 signaling pathway in microglia ( He et al, 2021 ).…”
Section: Sirtuin Activators For the Prevention Of Alzheimer’s Diseasementioning
confidence: 99%